Kelayakan Aksesoris Pengantin Bugis Dari Limbah Kaleng Biskuit - Afifah, Nawar Syadza; Setyowati, Erna; Indrian, Yulanda (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
Abstract. Cans are a container that is widely used in various industries as a material for packaging drinks and food. Right in Cikarang, many food and beverage industries use cans as packaging, which results in canned waste always increasing and becoming environmental pollution. The fix is ​​to use recycling. Recycling canned waste can produce new products that are useful, have artistic value and have sale value. The aim of the research was to determine the validity and feasibility of Bugis bridal accessories from biscuit tin waste. The research method uses an experiment with a one-group pretest-posttest design. Data collection techniques using documentation and observation. Based on the validity test and preference test conducted by 3 expert panelists and 15 slightly trained panelists. The analysis technique in this research uses descriptive percentages. The results of the validity test stated that the Bugis bridal accessories were very valid with an average of 90%. The results of the preference test stated that the Bugis bridal accessories were highly favored with an average of 92%. In conclusion, biscuit tin waste material is suitable as Bugis bridal accessories. Keywords: Waste, Biscuit Cans, Bugis Bridal Accessories. Abstrak. Kaleng merupakan tempat yang banyak dipergunakan di berbagai industri sebagai bahan untuk mengemas minuman maupun makanan. Tepat di Cikarang banyak industri makanan dan minuman yang menggunakan kaleng sebagai kemasan, yang mengakibatkan limbah kaleng selalu bertambah dan menjadi pencemaran lingkungan. Cara mengatasinya dapat menggunakan daur ulang. Mendaur ulang limbah kaleng dapat menghasilkan produk baru yang bermanfaat, bernilai seni dan terdapat nilai jual. Tujuan penelitian adalah mengetahui validitas dan kelayakan Aksesoris Pengantin Bugis dari limbah kaleng biskuit. Metode penelitian menggunakan eksperimen dengan desain one-grup pretest-postest. Teknik pengumpulan data menggunakan dokumentasi dan observasi. Berdasarkan uji validitas dan uji kesukaan dilakukan oleh 3 panelis ahli dan 15 panelis agak terlatih. Teknik analisis dalam penelitian menggunakan deskriptif persentase. Hasil uji validitas menyatakan bahwa Aksesoris Pengantin Bugis sangat valid dengan rata-rata 90%. Hasil uji kesukaan menyatakan bahwa Aksesoris Pengantin Bugis sangat disukai dengan rata-rata 92%. Simpulan bahan limbah kaleng biskuit layak sebagai Aksesoris Pengantin Bugis. Kata kunci: Limbah, Kaleng biskuit, Aksesoris Pengantin Bugis.